Perioperative Antibiotics in the Setting of Oropharyngeal Reconstruction: Less Is More. Issue 6 (June 2016) - Cohen, Leslie E.; Finnerty, Brendan M.; Golas, Alyssa Reiffel; Ketner, Jill J.; Weinstein, Andrew; Boyko, Tatiana; Rohde, Christine H.; Kutler, David; Spector, Jason A.
Abstract : Background: Recipient-site infection after oropharyngeal reconstruction is a potentially disastrous complication. Although studies suggest that perioperative antibiotics reduces infection rates in these patients from 87% to 20%, there is no consensus regarding what constitutes the most appropriate antibiotic regimen and duration of treatment. Methods: A retrospective review of perioperative antibiotic administration was performed of all patients who underwent local, pedicled, or free flap oropharyngeal reconstruction after oncologic resection by a single surgeon at a single institution between 2007 and 2013 to assess for recipient-site complications. Results: Ninety-seven patients underwent 100 reconstructions (61 free flap reconstructions, 39 pedicled/local flap reconstructions) and all received a combination of intravenous (IV) antibiotic agents designed to cover oral flora. There were 23 (23%) recipient-site complications, which included cellulitis (9%), mucocutaneous fistula (5%), abscess (5%), and wound dehiscence (4%). Duration of antibiotic prophylaxis, defined as less than 48 hours (short-course) or greater than 48 hours (long-course), was not a significant predictor of recipient-site complication. Significant risk factors for recipient-site complications were clindamycin prophylaxis ( P < 0.008), increased duration of surgery ( P < 0.047), and advanced age ( P < 0.034). Recipient-site complication was found to be a significant predictor of both increased length of hospital stay ( P < 0.001) and increased time to the resumption of enteral feeds ( P < 0.035). Conclusions: These data suggest that extended courses of perioperative antibiotics do not confer additional benefits in patients undergoing oropharyngeal reconstruction. We recommend a limited 48-hour course of prophylactic antibiotics with sufficient aerobic and anaerobic coverage to help minimize the incidence of antibiotic-related morbidities.